Navigating the Controversies of Retromer-Mediated Endosomal Protein Sorting - Tu, Yingfeng; Seaman, Matthew N. J. (Frontiers in Cell and Developmental Biology, 2021)
The retromer complex was first identified more than 20 years ago through studies conducted in the yeast Saccharomyces cerevisiae. Data obtained using many different model systems have revealed that retromer is a key component of the endosomal protein sorting machinery being necessary for recognition of membrane ‘cargo’ proteins and formation of tubular carriers that function as transport intermediates. Naturally, over the course of time and with literally hundreds of papers published on retromer, there have arisen disparities, conflicting observations and some controversies as to how retromer functions in endosomal protein sorting - the most note-worthy being associated with the two activities that define a vesicle coat: cargo selection and vesicle/tubule formation. In this review, I will attempt to chart a course through some of the more fundamental controversies to arrive at a clearer understanding of retromer.